Evaluation of a Novel PCR-Based Assay for Detection and Identification of Chlamydia trachomatis Serovars in Cervical Specimens - Quint, Koen (2007)
The aims of this study were to compare a novel PCR-based Chlamydia trachomatis detection and genotyping (Ct-DT) assay with the FDA-approved, commercially available C. trachomatis detection Hybrid Capture 2 (HC2) assay and to investigate the C. trachomatis serovar distribution among young women in a rural Costa Rican study population. A total of 5,828 sexually active women participating in a community-based trial in Costa Rica were tested for C. trachomatis by HC2. A sample of 1,229 specimens consisting of 100% HC2 C. trachomatis-positive specimens (n 827) and a random sample of 8% HC2 C. trachomatis-negative specimens (n 402) were tested with the Ct-DT assay. Agreement between the two assays was determined by the unweighted kappa statistic. Discrepant specimens were tested with a second commercially available test (COBAS TaqMan). The Ct-DT-positive specimens were further analyzed with the Ct-DT genotyping step to investigate the distribution of 14 different C. trachomatis serovars (A, B/Ba, C, D/Da, E, F, G/Ga, H, I/Ia, J, K, L1, L2/L2a, and L3). After accounting for the sampling fraction selected for Ct-DT testing, crude agreement with the HC2 assay was 98% and the kappa was 0.92 (95% confidence interval [CI], 0.89 to 0.97). The 33 discordant samples that were further analyzed with the COBAS TaqMan test showed better agreement with the Ct-DT assay (31/33, P < 0.001). Among the 806 Ct-DT-positive samples, serovar E was the most common serovar (31%), followed by serovars F and D (both 21%) and serovar I (15%). In conclusion, the novel Ct-DT assay permits reliable detection and identification of C. trachomatis serovars.